Past Performance dan Present Goal Tenaga Penjual yang di Moderasi Oleh Workforce Philosophy dan Workforce Conducivenes pada PT Asco Daihatsu Surabaya - Fani Firmansyah; Puji Endah Purnamasari (IQTISHODUNA, 2019)
Sales force can be said as the forefront of the company's sales. Without effective sales force sales, companies cannot consistently satisfy their shareholders. The purpose of this study was to examine the effect of Past Performance variables on the level of current sales performance, the influence of the variable understanding of corporate philosophy is able to strengthen the relationship between Past Performance and sales performance in the present and the influence of conducive company condition variables will be able to strengthen the relationship between performance the past with present sales performance. The results show that when past employee performance tends to increase, the number of present sales performance also tends to increase. The more employees understand the company's philosophy, the more sales performance of PT ASCO Prima Mobilindo (Daihatsu) Surabaya and Jember Branch products, and the presence of a conducive environment at PT ASCO Prima Mobilindo (Daihatsu) Surabaya Branch and Jember Branch does not have a significant effect on sales performance company